BELAJAR SEJARAH NKRI JADI SERU: PENGEMBANGAN MICROSITE INTERAKTIF PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SD - Muhammad Gazali; Riska Pristiani; Oktaviani Adhi Suciptaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an interactive learning media based on a microsite for teaching Pancasila Education, specifically the history of the Unitary State of the Republic of Indonesia (NKRI), for 4th grade elementary school students. The development followed the 4-D model (Define, Design, Develop, and Disseminate). The research subjects were 5th grade students at SD Muhammadiyah 1 Kawi, Malang. Data were collected through expert validation questionnaires, student and teacher practicality assessments, and effectiveness tests based on student learning outcomes. The findings indicate that the developed learning media is highly valid (average 90%), very practical (average 94%), and highly effective (85% classical learning completeness). The microsite includes interactive multimedia elements such as videos, quizzes, and educational games that enhance students’ understanding and interest in Pancasila material. Thus, this media is feasible and recommended as an innovative alternative in elementary school learning processes.